Research on Technology of Optical Switch Devices with Integrated Tunable Filters - HU Di; XIAO Qingming; ZHENG Jie (Guangtongxin yanjiu)
【Objective】In Reconfigurable Optical Add Drop Multiplexer (ROADM) downstream transmission, Tunable Optical Filters (TOF) are used to dynamically select wavelengths within a certain optical bandwidth range. By performing wavelength selection filtering and optical intensity attenuation equalization at the output ports of Wavelength Selective Switches (WSS) or Multicast Switches (MCS), the optical intensity at each output port of the ROADM is made consistent. MCS operates based on the Optical Switch (OSW) principle, enabling fast, accurate, and reliable transmission of multicast data by simultaneously switching multiple input channels to one or more output ports. Currently, most MCSs need to work in conjunction with TOF arrays to avoid accidental channels and ensure that the power entering the receiver after the MCS does not saturate or experience severe crosstalk. Most current TOF arrays are large, making integration with MCS difficult, thus affecting the realization of Colorless, Directionless and Contentionless (CDC)-ROADM. To reduce the implementation complexity of the ROADM downstream transmission system, it is necessary to address the issue of bulky module sizes. Therefore, this article designs an OSW device integrated with TOF functionality to reduce the size of the MCS module and optimize its structure.【Methods】The article integrates TOF functionality into the MCS module and designs a device that can achieve both optical channel selection and optical wavelength selection functions simultaneously. It is noted that Micro Electro Mechanical Systems (MEMS) can respectively realize the functions of OSW and TOF, and MEMS devices are relatively easy to implement with advantages such as fast tuning speed, wide tunable range, and small size. The article designs a new device combining both functions based on existing MEMS OSW and TOF solutions. This device is based on MEMS technology and is equipped with a multi-fiber collimator, enabling the X and Y axes of the device to respectively realize OSW and TOF functions with minimal mutual interference. The article introduces the basic principles and optical structure of this device and conducts optical design and simulation verification.【Results】Simulation results show that the device has good optical performance and can meet the usage requirements of MCS devices.【Conclusion】The MCS module using the TOF-OSW device proposed in the article integrates the TOF function, thereby saving the cost and space of the original TOF, reducing costs, space occupation, and system complexity. Therefore, the TOF-OSW device has broad application prospects and practical demand, better meeting the ROADM system's need for implementing CDC functionality.